Development of Project Assessment Instruments Based on E-Portfolio to Measure High School Student’s Creative Thinking Skills - Simamora, Mona Yelly; Sarwi,; Situmorang, Prima Lestari (Jurnal Paedagogy, 2026)
This study aims to develop an e-portfolio-based project assessment instrument for economics learning that can measure high school students’ creative thinking skills. The research employed a Research and Development (R&D) method using a modified 4D development model, consisting of the Define, Design, and Develop stages, followed by field testing. The research instruments included interview guidelines, validation sheets, creative thinking skills assessment rubrics, and response questionnaires. The research subjects consisted of three expert validators and 28 tenth-grade high school students in Jayapura City. The validity of the developed instrument was analyzed using Aiken’s V coefficient, resulting in an average value of 0.83, indicating a high level of validity. The field test results showed that students’ creative thinking skills were categorized as creative and highly creative. The internal consistency analysis using Cronbach’s Alpha produced a reliability coefficient of 0.89, indicating a high reliability level. The practicality evaluation based on student and teacher responses obtained a score of 92.5%, demonstrating that the instrument was practical for implementation. Furthermore, the effectiveness analysis was conducted by comparing pretest and posttest scores using normalized gain (N-Gain) analysis, which resulted in a gain score of 0.57, categorized as moderately effective. Therefore, the developed e-portfolio-based project assessment instrument is considered valid, reliable, practical, and effective for measuring students’ creative thinking skills in high school economics learning.